A comparative study of thermal performance in three generations of Iranian residential buildings: Case studies in Csa Gorgan. (January 2021) - Moolavi Sanzighi, Shima; Soflaei, Farzaneh; Shokouhian, Mehdi
This article focuses on evaluating thermal performance of different types of residential buildings in Mediterranean climate (Csa) of Iran. The aim is to identify the main design parameters in nine research cases, selected from three distinct periods of history with different architectural styles, and evaluating thermal performance of these buildings. To that end, a library study was carried out to identify the most influential passive design strategies and to highlight their impact on thermal comfort and energy efficiency of residential buildings. A field survey was conducted to determine the most common types of average-income houses in Csa climate of Gorgan, Iran, with a historical overview from 19th century to present. Nine buildings were selected to study from three different period of times including the years from 1850 to 1925, 1925 to 1979 and 1979 to present. A three-dimensional numerical model was developed to assess the impact of four main design parameters including orientation, geometrical properties, openings and materials on indoor thermal comfort for each case, using Design Builder commercial software package. The correlation between these design variables and thermal comfort was presented; the results reveal that the contemporary residential buildings are not designed as efficient as traditional houses in this area, in terms of passive energy saving techniques.